PERUBAHAN PERATURAN MENTERI PERTANIAN REPUBLIK INDONESIA NO.26/PERMENTAN/OT.140/2/2007 MENJADI NO. 98 /PERMENTAN/OT.9/2013 DAN PENGARUHNYA TERHADAP PERTAMBAHAN INDUSTRI PENGOLAHAN KELAPA SAWIT DI KABUPATEN LABUHAN BATU UTARA - Elikson Rumahorbo; Alvi Syahrin; Pendastaren Tarigan; Mahmul Siregar (Universitas Sumatera Utara, 2016)
ABSTRACT The development of oil palm plantations in Indonesia has affected the economic development in Indonesia. But economic development is only felt by group of companies. This is caused by the regulations do not give justice to all parties. Changes in Regulation of the Minister of Agriculture of the Republic of Indonesia No.26 / 2007 called Permentan meyebutkan that to build a palm oil mill must have the raw material from its own oil palm plantations at least 20%, these regulations become an obstacle to the development of palm oil mills, because in fact no longer available land for built new plantations. Therefore Permentan converted into Permentan 98/2013, which allowed the construction of palm oil mills without gardens on condition makes sustainable cooperation with the oil palm growers. Company owner IUP-P is also required to facilitate people palm garden development, environmental and social responsibility, and shall divide the shares ownership of the factory to the farmers as a supplier of raw materials. The government of Labuhan Batu Utara district has issued a permit to build a palm oil mill without a garden called IUP-P as much as 3 units. Construction of palm oil mills have brought benefits to the oil palm growers. However, in the implementation of IUP-P in Labuhan Batu Utara district government lacks transparency in terms of time, cost and procedures for the issuance of permits IUP-P. Less government involve the community in the process of issuing permits this could lead to losses because investors are becoming less interested in investing. The government should be able to apply the principles of good governance, namely the principle of transparency, accountability and good governance in order to invest more advanced. Key words: (1) Licensing, (2) the Government, (3) Development of Palm Oil Processing Industry